Self-organized practices for complex urban transformation. The case of Bagnoli in Naples, Italy - Ragozino, Stefania; Varriale, Andrea; Esposito De Vita, Gabriella (Tracce urbane. Rivista italiana transdisciplinare di studi urbani, 2018)
The current political instability and economic uncertainty slow down and complicate urban transformations and their correspondent decisional processes. At the same time, however, “austerity urbanism” pushes cities to explore alternative policy-making approaches that might include new actors in the policy network. We investigate this democratic potentiality by analyzing different configurations of actors (2002-2016) that have been participating in the over two decades-long, and still incomplete, transformation of a former industrial area in Bagnoli, in western Naples (Italy). In 2015, the central Government took over the city’s planning competences over the area. In response, several social movements have intensified their action against what they regard as an unchecked, “neo-liberal” transformation of the area. The compatibility of the respective views, as well as pragmatic considerations, led to an alignment between movements and the city and to their joint opposition to the Government. This configuration, we argue, makes room for usually excluded actors and is thus an innovative way of urban policy making.